Invasive Fungal Infection After Lung Transplantation: Epidemiology in the Setting of Antifungal Prophylaxis. (25th February 2019) - Baker, Arthur W; Maziarz, Eileen K; Arnold, Christopher J; Johnson, Melissa D; Workman, Adrienne D; Reynolds, John M; Perfect, John R; Alexander, Barbara D
Abstract: Background: Lung transplant recipients commonly develop invasive fungal infections (IFIs), but the most effective strategies to prevent IFIs following lung transplantation are not known. Methods: We prospectively collected clinical data on all patients who underwent lung transplantation at a tertiary care academic hospital from January 2007–October 2014. Standard antifungal prophylaxis consisted of aerosolized amphotericin B lipid complex during the transplant hospitalization. For the first 180 days after transplant, we analyzed prevalence rates and timing of IFIs, risk factors for IFIs, and data from IFIs that broke through prophylaxis. Results: In total, 156 of 815 lung transplant recipients developed IFIs (prevalence rate, 19.1 IFIs per 100 surgeries, 95% confidence interval [CI] 16.4–21.8%). The prevalence rate of invasive candidiasis (IC) was 11.4% (95% CI 9.2–13.6%), and the rate of non- Candida IFIs was 8.8% (95% CI 6.9–10.8%). First episodes of IC occurred a median of 31 days (interquartile range [IQR] 16–56 days) after transplant, while non- Candida IFIs occurred later, at a median of 86 days (IQR 40–121 days) after transplant. Of 169 IFI episodes, 121 (72%) occurred in the absence of recent antifungal prophylaxis; however, IC and non- Candida breakthrough IFIs were observed, most often representing failures of micafungin (n = 16) and aerosolized amphotericin B (n = 24) prophylaxis, respectively. Conclusions: Lung transplant recipients at our hospital had high rates of IFIs, despite receiving prophylaxis with aerosolized amphotericin B lipid complex during the transplant hospitalization. These data suggest benefit in providing systemic antifungal prophylaxis targeting Candida for up to 90 days after transplant and extending mold-active prophylaxis for up to 180 days after surgery. Abstract : Lung transplant recipients experienced high rates of invasive fungal infection, despite receiving prophylaxis with aerosolized amphotericin B lipid complex during the transplant hospitalization. Antifungal prophylaxis after lung transplantation should include coverage for invasive candidiasis and prolonged prophylaxis against respiratory molds.